Electronic structure and magneto-optical Kerr effect in UCuAs₂ - Antonov, V.N.; Harmon, B.N.; Horpynyuk, O.; Yaresko, A.N. (Физика низких температур, 2003)
The optical and magneto-optical (MO) spectra of the ternary compound UCuAs₂ are investigated theoretically from first principles, using the fully relativistic Dirac linear-muffin-tin-orbital band structure method. The electronic structure is obtained with the local spin-density approximation (LSDA), as well as with the so-called LSDA+U approach. Better agreement between the theoretically calculated and the experimentally measured MO Kerr spectra is found with the LSDA+U approximation. The origin of the Kerr rotation in the compound is examined.